A lipophilic copper(ii) complex as an optical probe for intracellular detection of NO. Issue 45 (28th October 2016) - Wilson, Neil; Mak, Lok Hang; Cilibrizzi, Agostino; Gee, Antony D.; Long, Nicholas J.; Woscholski, Rudiger; Vilar, Ramon
Abstract : A new copper(ii ) complex has been prepared and used as chemical sensor for the optical imaging of NO in cells. Abstract : A new chemical sensor for cellular imaging of NO is presented. This cell-permeable probe is based on a complex where copper(ii ) is coordinated to a tridentate ligand substituted with a fluorophore (NBD) and an octyl group. The fluorescence response of this complex towards a range of reactive species (namely NO, NO2 −, NO3 −, H2 O2, ClO −, O2 − and ONOO − ) has been studied in vitro showing that the probe is highly selective for NO. The probe is readily taken up by cells and is able to image the cellular concentrations of NO.